A lőcsei líceum történeti áttekintése - Czenthe, Miklós (Gerundium, 2017)
Historical Overview of the Lyceum of Leutschau. The script summerizes the story of the Lutheran lyceum in Leutschau, based on the Lutheran archives from there. Between 1544–1674 the whole city was Lutheran, the secondary grammer-school reached a high level, lead from the rector, who was financed by the city-administration. In the time of the counter-reformation the Lutheran community tried to keep up their school, which was financed by the German burgher. At the time of rector Marton Liedemann,  1793–1813 developped the lyceum, on the highest degree were taught philosophy and theology on high-school level. The building of the school became the sc. Hain-house on the market-place. Because of financial problem since 1859 became the school a „state Lutheran grammer-school”, from 1869 a state „Hauptrealschule”. The lyceal library remained at the Lutheran congregation, it has develepped to the famous Lutheran library and archives of Leutschau, which contained material not only for the Lutheran, bot also for the burgher and the city.